Guidance algorithm for complex-shape peg-in-hole strategy based on geometrical information and force control. (17th April 2016) - Song, Hee-Chan; Kim, Young-Loul; Song, Jae-Bok
Abstract: This paper suggests a solution for peg-in-hole problems involving complex geometry. Successful completion of peg-in-hole assembly tasks depends on a geometry-based approach for determining the guiding direction, fine contact motion control, and a reference force for the alignment/insertion process as well. Therefore, in this study, we propose a peg-in-hole strategy for complex-shaped parts based on a guidance algorithm. This guidance algorithm is inspired by the study of human motion patterns; that is, the assembly direction selection process and the maximum force threshold are determined through the observation of humans performing similar actions. In order to carry out assembly tasks, an assembly direction is chosen using the spatial arrangement and geometric information of complex-shaped parts, and the required force is decided by kinesthetic teaching with a Gaussian mixture model. In addition, an impedance controller using an admittance filter is implemented to achieve stable contact motion for a position control-based industrial robot. The performance of the proposed assembly strategy was evaluated by experiments using arbitrarily complex-shaped parts with different initial situations. Abstract :